Thyroid profile in women with menstrual disorders - Digra, Madhu; Kumar, Ravinder; Kumar, Dinesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thyroid dysfunction influences both menstrual flow and fertility, likely through changes in sex hormone levels, gonadotrophin release and possibly ovarian function. Objectives of this work were to study thyroid related complaints and thyroid function tests in patients with menstrual irregularities like menorrhagia, oligomenorrhoea, amenorrhoea, hypomenorrhoea and ploymenorrhoea, to study menstrual patterns in women with diagnosed thyroid disease-hypothyroidism/hyperthyroidism and to study changes in menstrual patterns, if any in these patients during the course of treatment of thyroid disease, who receive correct treatment Methods: This study was conducted in the Department of Obstetrics and Gynecology in Government L.D. Hospital, Government Medical College, Srinagar during the period from 2006 to 2007. There were two groups under which the study was conducted. Group A: Seventy-five patients of DUB from Department of Gynecology in reproductive age group (15-45 years) presenting with menstrual irregularities like menorrhagia, oligomenorrhoea, amenorrhoea, hypomenorrhoea and ploymenorrhoea were studied for thyroid profile. Group B comprised of 25 patients including already diagnosed 17 hypothyroid and 8 hyperthyroid patients. The study protocol included thorough history taking, general physical examination, meticulous per speculum and pelvic examination and routine investigations like Hb, BT, CT, TLC, DLC, Platelet count and ABO-Rh in all patients, Serum T3, T4, TSH estimation. Results: Most of the patients were in 35-45 years age group. Prevalence of infertility was more in hypothyroid group. 22.66% patients with DUB were detected as hypothyroid where as 13.33% patients were detected as hyperthyroid. Conclusions: Thyroid function tests, many of which are sensitive radioimmunoassay, radiometric assays and even new chemiluminescence method, which can detect minute changes in hormone levels must be done in women presenting with menstrual disorders.